The Distance Between the “Self” and the “Other” in Children’s Digital Books - Kucirkova, Natalia; Littleton, Karen (Frontiers in Psychology, 2020)
This conceptual paper contributes towards our understanding of the underlying mechanisms in children’s understanding of self and the other with media. We synthesise diverse bodies of literature, concerned with children’s reading with digital and traditional (print) books, to explicate the parameters that may, in part, explain positive learning outcomes and further illuminate the patterns across various measures. We propose the “Distance Model”, which suggests that a child’s interest in a reading activity depends on its proximity to the child’s funds of identity (Esteban-Guitart & Moll, 2014). The closer the proximity, the more salient the impact on the child’s cognitive understanding and sense of belonging. The familiarity of the reading content and the relevance of the reading medium for a child’s personal life can be evoked through a number of reading strategies and design techniques, which we discuss in relation to children’s literature and the contemporary design of children’s interactive e-books. We conclude with some suggestions regarding future applications of the Distance Model in children’s media research.